Development a Caring Model of Critically Ill Surgical Patients with Difficult Weaning Using ABCDEF-R Bundle - Pukkham, Kanjana (Thai Journal of Nursing and Midwifery Practice, 2022)
Abstract: This research and development aimed to develop and evaluate a model for critically ill surgical patients with difficult weaning by using ABCDEF-R bundle in a surgical intensive care unit of Maharaj Nakhon Si Thammarat Hospital. Participants in the project were divided into 2 groups: 21 nurses caring for critically ill patients and 85 critically ill surgical patients, 40 people were in the pre-implementing group and 45 were in the post-implementing group. The research instruments were: 1) demographic and illness data records, 2) assessment of knowledge about weaning from a ventilator, 3) the assessment of practical feasibility and easily/difficulty in using model, 4) the risk assessment of difficult weaning, 5) the assessment of clinical and organization’s outcomes and 6) procedure manual based on ABCDEF-R bundle activities. Data were analyzed using descriptive and comparative statistics. Results showed that nurses’ knowledge after model implementation and two-month follow-up was significantly higher than before model implementation (p < .05). The model was feasible and easy to implement in practice for all 7 categories at high and very high level (> 80%). The clinical outcomes after model implementing were better than before regarding the significantly decrease of weaning time (p= .021), the number of mechanical ventilation days (p= .04), the incidence of ventilator associated pneumonia (p= .025) and the length of stay in ICU (p= .036). It is concluded that caring for critically ill surgical patients with difficult weaning by using the ABCDEF-R bundle can improve the care quality and some clinical outcomes. However, it should be followed up in long term.